2022
DOI: 10.3390/antibiotics11060732
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftolozane-Tazobactam and Other Antibiotics against Pseudomonas aeruginosa Infection-Isolates from an Academic Medical Center in Thailand

Abstract: (1) Background: Resistant Pseudomonas aeruginosa (PA) infections have limited treatment options. Data on the activity of ceftolozane-tazobactam (C-T) against PA in Thailand are limited. Objectives: The objective of this study was to identify the in vitro activity of C-T against general and resistant PA isolates from patients with real clinical infections from the HRH Princess Maha Chakri Sirindhorn Medical Center (MSMC) compared to other antibiotics and to study the resistant molecular patterns of those PA str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…One isolate showed that C/T was the only susceptible antibiotic compared to other antibiotic groups, including carbapenem (meropenem and imipenem). This finding aligns with a previous study that reported that Pseudomonas non-susceptible to meropenem may still be susceptible to C/T [20][21][22]. The high susceptibility against carbapenem-resistant P. aeruginosa was also reported by other studies [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…One isolate showed that C/T was the only susceptible antibiotic compared to other antibiotic groups, including carbapenem (meropenem and imipenem). This finding aligns with a previous study that reported that Pseudomonas non-susceptible to meropenem may still be susceptible to C/T [20][21][22]. The high susceptibility against carbapenem-resistant P. aeruginosa was also reported by other studies [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…A high percentage of strains was confirmed susceptible to tobramycin (91.0%) and ceftazidime (78.0%) too. Similar results were obtained by Tantisiriwat et al [ 27 ] for the strains isolated from different types of clinical samples. Among 100 isolates, 94.0% were susceptible to C/T, and 18.0% were defined as MDR.…”
Section: Discussionsupporting
confidence: 90%
“…Also within this Special Issue, Losito AR et al discuss treatment options for difficult-to-treat P. aeruginosa , namely: novel β-lactam/β-lactamase-inhibitor combinations (ceftolozane/tazobactam, ceftazidime/avibactam and imipenem/relebactam, as well as combinations in the pipeline), cefiderocol, and fosfomycin-based combinations [ 8 ]. Of particular note is that ceftolozane/tazobactam activity may be reduced against P. aeruginosa isolates co-resistant to all other anti-pseudomonal β-lactams, as shown by Tantisiriwat W et al [ 9 ]. Moreover, none of the currently available β-lactam/β-lactamase combinations are active against metallo-β-lactamase producing P. aeruginosa [ 3 ].…”
mentioning
confidence: 99%